2017
DOI: 10.1016/j.freeradbiomed.2017.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular superoxide dismutase and its role in cancer

Abstract: Reactive oxygen species (ROS) are increasingly recognized as critical determinants of cellular signaling and a strict balance of ROS levels must be maintained to ensure proper cellular function and survival. Notably, ROS is increased in cancer cells. The superoxide dismutase family plays an essential physiological role in mitigating deleterious effects of ROS. Due to the compartmentalization of ROS signaling, EcSOD, the only superoxide dismutase in the extracellular space, has unique characteristics and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 229 publications
(271 reference statements)
0
124
0
1
Order By: Relevance
“…SOD is a type of primary cellular antioxidant catalyzing the conversion of superoxide to H 2 O 2 , which has been proven to favor tumor progression (12). There are three members of the SOD family present in mammals, namely CuZnSOD, MnSOD and extracellular SOD (EC-SOD), which are located in different places inside or outside the cell (28). Epidemiological evidence has indicated that increased levels of SOD were observed in several tumor types along with tumor progression from early-stage (non-invasive) to late-stage (metastatic) (29).…”
Section: Discussionmentioning
confidence: 99%
“…SOD is a type of primary cellular antioxidant catalyzing the conversion of superoxide to H 2 O 2 , which has been proven to favor tumor progression (12). There are three members of the SOD family present in mammals, namely CuZnSOD, MnSOD and extracellular SOD (EC-SOD), which are located in different places inside or outside the cell (28). Epidemiological evidence has indicated that increased levels of SOD were observed in several tumor types along with tumor progression from early-stage (non-invasive) to late-stage (metastatic) (29).…”
Section: Discussionmentioning
confidence: 99%
“…For example, tumors associated macrophages have been shown to induce sub-lethal oxidative stress in murine mammary cancer cells, maybe through the secretion of TNF-α. On the other hand, extracellular superoxide dismutases might finely tuning the levels of H 2 O 2 in the extracellular milieu altering the proliferation and differentiation of immune cells ( 200 ). In fact, ROS may induce decreased viability in CD4+ T lymphocytes and the inhibition of DNA synthesis ( 181 , 201 ).…”
Section: Redox Control Of Cellular Fatementioning
confidence: 99%
“…Superoxide radical is produced by the single electron reduction of the oxygen molecule. This reactive free radical is rapidly converted to hydrogen peroxide via superoxide dismutase (SOD), which is the only enzyme that scavenges superoxide [5]. Hydrogen peroxide is also a highly reactive molecule that is broken down into water by 2 types of enzymes, catalase (CAT) and glutathione peroxidase (GPx).…”
Section: Introductionmentioning
confidence: 99%